Identifikasi Karakter Morfologi Caplak Rhipicephalus sanguineus (sensu lato) di Kota Bitung, Sulawesi Utara: Morphological Character Identification of Rhipicephalus sanguineus (sensu lato) ticks in Bitung, North Sulawesi. - Tahulending , Jane (Perkumpulan Entomologi Kesehatan Indonesia, 2024)
Riphicephalus sanguineus is a species of tick from the family Ixodidae (hard tick), consisting of two families, namely Ixodidae and Argasidae. Rhipicephalus is an ectoparasite of the class Acari, and acts as a vector of viruses, bacterial infections, and parasitic diseases. The R. sanguineus tick is an important vector that plays a role in health problems that arise in humans and animals. Research on Riphicephalus in Indonesia is still rare, especially related to its morphology and genetics. This study aims to identify the morphological character of the R. sanguineus tick. Total of 150 tick specimens were collected from three locations in Bitung City over three months, collected by hand collecting method on local dogs and identified to the species level based on their morphological characteristics. The specimen belongs to a single species of the genus Rhipicephalus. This study provides detailed description of the results of measurements body areas such as gnatosome, idiosoma, capitation base, stactum, and spiracle obtained to provide details related to morphological variation. There were variations in the measurement of the body area of the R. sanguineus tick at the three research locations.